Advective Heat Transport and the Salt Chimney Effect: A Numerical Analysis - David P. Canova; Mark P. Fischer; Richard S. Jayne; Ryan M. Pollyea (Geofluids)
We conducted numerical simulations of coupled fluid and heat transport in an offshore, buried salt diapir environment to determine the effects of advective heat transport and its relation to the so-called “salt chimney effect.” Model sets were designed to investigate (1) salt geometry, (2) depth-dependent permeability, (3) geologic heterogeneity, and (4) the relative influence of each of these factors. Results show that decreasing the dip of the diapir induces advective heat transfer up the side of the diapir, elevating temperatures in the basin. Depth-dependent permeability causes upwelling of warm waters in the basin, which we show to be more sensitive to basal heat flux than brine concentration. In these model scenarios, heat is advected up the side of the diapir in a narrower zone of upward-flowing warm water, while cool waters away from the diapir flank circulate deeper into the basin. The resulting fluid circulation pattern causes increased discharge at the diapir margin and fluid flow downward, above the crest of the diapir. Geologic heterogeneity decreases the overall effects of advective heat transfer. The presence of low permeability sealing horizons reduces the vertical extent of convection cells, and fluid flow is dominantly up the diapir flank. The combined effects of depth-dependent permeability coupled with geologic heterogeneity simulate several geologic phenomena that are reported in the literature. In this model scenario, conductive heat transfer dominates in the basal units, whereas advection of heat begins to affect the middle layers of the model and dominates the upper units. Convection cells split by sealing layers develop within the upper units. From our highly simplified models, we can predict that advective heat transport (i.e., thermal convection) likely dominates in the early phases of diapirism when sediments have not undergone significant compaction and retain high porosity and permeability. As the salt structures mature into more complex geometries, advection will diminish due to the increase in dip of the salt-sediment interface and the increased hydraulic heterogeneity due to complex stratigraphic architecture.